Pro Service-Oriented Smart Clients with .NET 2.0 - Hashimi, Sayed Y. (Apress, 2012)
This book shows you how to build smart client applications and how to exploit them using a service-oriented architecture. So, the best way to introduce the book is to define just what a smart client is.